Cultural Expression in Batik: An Analysis of Writing and Motifs - Rizal Fauzi; Mia Maarif (Jurnal Inovasi dan Kreativitas (JIKa), 2024)
Problems: This study aims to explore the role of batik as a medium of cultural expression by focusing on the analysis of motifs and writing about batik. The primary issue addressed is how batik motifs, such as "Parang," "Mega Mendung," and "Cikadu," function as visual texts conveying cultural messages, and how writing about batik plays a role in interpreting and disseminating these meanings. The objective of the research is to understand the relationship between batik motifs and the writing about batik in the context of preserving and developing cultural values. Methodology: employs a qualitative approach, combining semiotic and narrative analysis methods. Semiotic analysis is used to interpret the symbolic meanings of batik motifs, while narrative analysis is employed to understand how writing about batik depicts and documents these values. The findings: reveal that batik motifs are not merely decorative patterns but complex visual communication tools that convey cultural values and life philosophies. Writing about batik functions as a written text that supports the documentation and dissemination of these meanings. The study also uncovers that the community holds a strong perception of batik as a cultural identity symbol that needs to be preserved. Innovations in batik motifs and writing indicate that batik is a dynamic cultural heritage capable of adapting to changing times. The results of this study make a significant contribution to efforts to preserve and develop batik as a rich and evolving cultural heritage. Keywords: cultural expression, batik motifs, semiotics, narrative